Exploring study skills and learning approaches among high school students in the southern Karnataka region - Fathima, Nidha; D., Sunil Kumar; J., Rakshitha; K. V., Krishnamurthy (International Journal Of Community Medicine And Public Health, 2025)
Background: Education is a fundamental right, and effective study skills are vital for academic success. Key skills include textbook reading, note-taking, concentration, test preparation, memory, and time management. This study aimed to assess study skills among high school students and examine their relationship with academic performance. Methods: A cross-sectional study was conducted between December 2022 and May 2023 among high school students in Mysuru and Chamarajanagar to assess study skills and learning strategies. A sample of 382 students was selected using probability proportionate to size sampling. Data were collected using a pre-tested questionnaire, including socio-demographics, academic performance, and the Dennis Congos study skills inventory (DCSSI), covering six domains: textbook reading, note-taking, memory, test preparation, concentration, and time management. Domain-specific thresholds identified areas needing improvement. Data analysis was done using SPSS v24 with descriptive and inferential statistics. Ethical approval and informed consent were obtained. Results: Among 382 high school students, most were aged 14-15 years (65.1%) and belonged to the upper-middle socioeconomic class (58.3%). Academic performance showed that 62.9% scored between 61-80%, while only 6% achieved scores above 90%. Students demonstrated strengths in test preparation (98.4%), concentration (66.8%), time management (54.7%), and textbook reading (58.1%), but showed deficits in note-taking (19.6%) and memory skills (12.6%). Textbook reading was significantly associated with academic performance (p=0.005), while time management approached significance (p=0.063). Conclusions: Study highlighted that textbook reading impacts performance; note-taking and memory need improvement.